Comparison of the Effectiveness of Intensive Short-Term Dynamic Psychotherapy and Schema Therapy on Cognitive Emotion Regulation and Experiential Avoidance in Female Patients with Generalized Anxiety Disorder - Dehpour , Abolfazl; Heydari, Shaban; Mirzaian , Bahram (KMAN Counseling & Psychology Nexus, 2026)
The aim of the present study was to compare the effectiveness of Intensive Short-Term Dynamic Psychotherapy (ISTDP) and Schema Therapy on cognitive emotion regulation and experiential avoidance in female patients diagnosed with Generalized Anxiety Disorder. Based on its objective, this study is applied in nature, and in terms of data collection, it was conducted cross-sectionally using a quasi-experimental design with a pretest–posttest control group and a three-month follow-up assessment. The statistical population consisted of women aged 20–45 with Generalized Anxiety Disorder who referred to counseling and psychological services centers in Tehran between June 2024 and October 2024. Data were collected using the Cognitive Emotion Regulation Questionnaire (CERQ-P) and the Acceptance and Action Questionnaire–II (AAQ-II), administered during the pretest, posttest, and follow-up phases to the sample group. Descriptive statistics (mean, standard deviation) and inferential statistics (mixed repeated-measures analysis) were used for data analysis. The findings indicated significant differences between the experimental and control groups in both treatment methods, and these differences remained stable at follow-up (p < .05). However, when comparing the effectiveness of the two therapeutic approaches, the results showed that Intensive Short-Term Dynamic Psychotherapy was more effective than Schema Therapy. Overall, the results suggest that both Intensive Short-Term Dynamic Psychotherapy and Schema Therapy can help reduce cognitive problems in individuals with Generalized Anxiety Disorder, and it may even be argued that ISTDP is more effective in reducing these cognitive difficulties. Given that one of the inclusion criteria in this study was the absence of pharmacotherapy, it is recommended that future studies combine medication with these two treatments to obtain more comprehensive results.